Terapi Relaksasi Nafas Dalam Pada ODGJ Yang Mengalami Perilaku Kekerasan Di Kota Bengkulu - Amrina Rosada; Febina Roviyanti; Evika Triani; Hafiz Hafiz; Hafizah Ramadani; Nelsy Astika; Ade Herman Sudereja (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
Mental disorders are health conditions in which the individual experiences changes in thought patterns, emotions, or behavior or a combination of these three changes (American Psychological Association. 2015). Keliat (2012), states that violent behavior is a person who is ambiguous, always anxious, has a negative assessment of himself and others, is unable to solve problems well, so that violent behavior is one of the methods used by patients to solve problems. Violent behavior is a situation where a person carries out actions that can cause physical harm, both to himself and others, characterized by uncontrolled rage and restless noise (Dermawan, 2018). The method used by the author in this case study is the interview technique. The sample taken in this case study was one person with a mental disorder at risk of violent behavior in the Bengkulu City area. The results of research that has been carried out show that teaching deep breathing relaxation techniques can reduce violent behavior towards ODGJ patients.